Effect of pH on simultaneous saccharification and isomerization by glucoamylase and glucose isomerase - Mishra A.; Debnath M. (My University, 2025)
pH and temperature play critical roles in multistep enzymatic conversions. In such conversions, the optimal pH for individual steps differs greatly. In this article, we describe the production of glucoamylase (from Aspergillus oryzae MTCC152 in solid-state fermentation) and glucose isomerase (from Streptomyces griseus NCIM2020 in submerged fermentation), used in industries for producing high-fructose syrup. Optimum pH for glucoamylase was found to be 5.0. For glucose isomerase, the optimum pH ranged between 7.0 and 8.5, depending on the type of buffer used. Optimum temperature for glucoamylase and glucose isomerase was 50 and 60°C, respectively. When both the enzymatic conversions were performed simultaneously at a compromised pH of 6.5, both the enzymes showed lowered activity. We also studied the kinetics at different pHs, which allows the two-step reaction to take place simultaneously. This was done by separating two steps by a thin layer of urease. Ammonia generated by the hydrolysis of urea consumed the hydrogen ions, thereby allowing optimal activity of glucose isomerase at an acidic pH of 5.0.